2014
DOI: 10.4196/kjpp.2014.18.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine Decreased Hippocampal Damage and Improved Vascular Risk Markers in a Rat Model of Pentylenetetrazole Induced Kindling Seizure

Abstract: Various antiepileptic drugs (AEDs) especially enzyme-inducing AEDs might be associated with increased vascular risk, through impairment of the endogenous antioxidative ability which may trigger oxygen-dependent tissue injury. Lamotrigine (LTG) a non-enzyme-inducing AED has scarce information regarding its effects on oxidative stress. The present study aimed to study the possible modulation of vascular risk factors of epileptogenesis by LTG, in a rat model of kindling seizure induced by pentylenetetrazole (PTZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Histopathological studies of the hippocampus tissues indicated that epilepsy induced by PTZ caused an obvious decrease in the number of the normal neurons, as evidenced by a decrease in its Nissl granules content compared with normal group, which was in agreement with previous studies [48]. However, Rb1 administration in the present study displayed a decrease in hippocampal damage through a significant increase in the Nissl granules content of the normal neurons, indicating that Rb1 protects against PTZ-induced hippocampal neuron damage.…”
Section: Discussionsupporting
confidence: 82%
“…Histopathological studies of the hippocampus tissues indicated that epilepsy induced by PTZ caused an obvious decrease in the number of the normal neurons, as evidenced by a decrease in its Nissl granules content compared with normal group, which was in agreement with previous studies [48]. However, Rb1 administration in the present study displayed a decrease in hippocampal damage through a significant increase in the Nissl granules content of the normal neurons, indicating that Rb1 protects against PTZ-induced hippocampal neuron damage.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have suggested that LTG decreased seizure severity and hippocampal CA3 region damage in PTZ‐kindled animals (Haggag, Hasanin, Raafat, & Abdel, ). Unfortunately, we did not find this reduction in neuronal cell apoptosis in the hippocampal CA3 region both in LTG and VPA treated animals in our study, which is consistent with a study on LTG and VPA in a status epilepticus model of rat pups (Halbsgut, Fahim, Kapoor, Hong, & Friedman, ).…”
Section: Discussionmentioning
confidence: 88%
“…Epilepsy is primarily caused by the inhibition of gamma-amino-butyric-acid (GABA) receptor, an inhibitory neurotransmitter in the neuronal synapse. Epileptogenesis induced by pentylenetetrazole (PTZ) caused a significant increase in serum hcy in comparison to control rats [32]. Unlüçerçi and colleagues [33] also reported increase of serum hcy levels in epilepsy.…”
Section: Discussionmentioning
confidence: 99%